Tristeza disease and its vectors in Israel: past and current status - Soroker V.; Sadovsky A.; Drishpon Y.; Wise M. (Citrus tristeza virus and Toxoptera citricidus: a serious threat to the Mediterranean citrus industry, 2009)
The historical review of Citrus tristeza findings in Israel is reported since 1956, showing the first outbreaks in 1970 by Aphis gossypii. After the failure of the virus eradication programme, tolerant rootstocks were used for the disease control. Nowadays very few declining trees are reported and, apparently, Toxoptera citricidus is not present yet. A national regulation provides preventive measures (primarily the use of CTV-free propagating materials) for the control of citrus tristeza.